Pengembangan E-Modul Laju Reaksi Discovery Learning Berbasis Blog Untuk Meningkatkan Motivasi Belajar dan Komunikasi Siswa: Analisis Kebutuhan - Nababan, Kartyka; Zega, Raih Sani (Oxygenius: Journal Of Chemistry Education, 2024)
This research is a preliminary study of the development of blog-based reaction rate e-module media to increase student learning motivation and communication which was carried out by R&D. This study is a mixed-method of descriptive qualitative and quantitative methods. Data was collected through library research and questionnaires which were processed using the Rasch Model. The results of data collection were then processed in a qualitative descriptive manner. The purpose of this study is to find out, describe and explain the need for blog-based e-module development on the subject of reaction rates and the advantages and disadvantages of blog media. The literature study was carried out by reviewing journals relevant to the research (library research) and questionnaire data collection was carried out online using the Google form. Based on the results of the questionnaire analysis for the development of blog-based reaction rate e-modules to increase student learning motivation and communication using the Rasch Model, the results obtained from reviewing journals and distributing questionnaires can be concluded that blogger media is classified as effective for use as an alternative learning media for students because it is easy to use, inexpensive and interactive. The use of blog media is able to increase student learning motivation because of the in-depth presentation of material. The advantage of using blog media compared to print media is the sub-microscopic presentation. The blog-based module is able to describe abstract sub-microscopic materials on reaction rates in detail and is not boring because it is animated. Along with the development of learning motivation, students’ mathematical communication and communication in the learning process will increase.